Fabrication of Zn and Ti-loaded Carbon-silica Composite Derived from Gelatin Template for the Photodegradation of Methylene Blue - Ulfa, Maria; Hasanah, Ika Uswatun; Setiarini, Ida (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Carbon-silica nanocomposites (CSNs) from gelatin as a carbon source and natural template and TEOS as a silica source have been successfully synthesized and impregnated into ZnO and TiO2 photocatalysts. The structural, morphological, and textural properties and photocatalytic activity for methylene blue degradation of TiO2/CSNs and ZnO/CSNs were investigated. XRD data revealed that TiO2/CSNs and ZnO/CSNs had different structural characteristics with similar crystallinity. FTIR spectra demonstrated the presence of Zn–O and Ti–OC bonds, respectively, at about 500-450 cm-1 and 1500 cm-1. The morphological surface exhibited stacked tubular shapes of TiO2/CSNs and ZnO/CSNs with the primary elements of Ti, Zn, Si, C, and O. The nitrogen adsorption-desorption curves revealed both micropores and mesopores of TiO2/CSNs and ZnO/CSNs where the surface area reduced due to the blocking pore after impregnation. Moreover, ZnO/CSNs verified a higher degradation percentage against methylene blue than that of TiO2/CSNs. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).